2018
DOI: 10.1038/s41557-018-0181-x
|View full text |Cite
|
Sign up to set email alerts
|

Carbopalladation of C–C σ-bonds enabled by strained boronate complexes

Abstract: Transition metal-catalysed cross-coupling reactions, particularly those mediated by palladium, are some of the most broadly used chemical transformations. The fundamental reaction steps of such crosscouplings typically include oxidative addition, transmetalation, carbopalladation of a -bond, and/or reductive elimination. Herein, we describe an unprecedented fundamental reaction step: a C−C σ-bond carbopalladation. Specifically, an aryl palladium(II) complex interacts with a −bond of a strained bicyclo[1.1.0]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
105
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 172 publications
(107 citation statements)
references
References 57 publications
(70 reference statements)
2
105
0
Order By: Relevance
“…[9,10] To develop ag eneral, complementary approach to access cyclobutylboronates,w e envisioned using ac opper-catalyzed conjugate borylation of cyclobutenones.P ioneering work by Hosomi [11] has shown that conjugate borylation provides an extremely efficient entry into optically enriched cyclopentyl-and cyclohexylboronates, [12,13] however the cyclobutane equivalent is lacking in the literature.T oaddress this void, we targeted the conjugate borylation of a,b-disubstituted cyclobutenones (Figure 2c), which would provide the first examples of enantioenriched tertiary cyclobutylboronates. [14] Furthermore,i tw ould also allow access to polysubstituted cyclobutanones,f or which catalytic enantioselective approaches remain scarce. [15] The expected keto-boronate products can undergo bidirectional functionalizations,making them valuable medicinal chemistry intermediates.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[9,10] To develop ag eneral, complementary approach to access cyclobutylboronates,w e envisioned using ac opper-catalyzed conjugate borylation of cyclobutenones.P ioneering work by Hosomi [11] has shown that conjugate borylation provides an extremely efficient entry into optically enriched cyclopentyl-and cyclohexylboronates, [12,13] however the cyclobutane equivalent is lacking in the literature.T oaddress this void, we targeted the conjugate borylation of a,b-disubstituted cyclobutenones (Figure 2c), which would provide the first examples of enantioenriched tertiary cyclobutylboronates. [14] Furthermore,i tw ould also allow access to polysubstituted cyclobutanones,f or which catalytic enantioselective approaches remain scarce. [15] The expected keto-boronate products can undergo bidirectional functionalizations,making them valuable medicinal chemistry intermediates.…”
mentioning
confidence: 99%
“…Protodeboronation resulted in the formal anti cyclobutenone hydrogenation product 8 in moderate yield and 10:1 dr. Thep otassium trifluoroborate salt 9 was obtained in ah igh 94 %y ield and was found to be as uitable substrate for ar hodium-catalyzed aldehyde addition to obtain diketone 10 as amixture of diastereomers upon oxidation. [27] Alternatively,t he corresponding ketal 11 can serve as av iable substrate for an umber of carbon-carbon bond forming processes.Z weifel olefination, alkynylation, and acetylation were possible in good to high yields (12)(13)(14), using previously established stereoselective lithiation-1,2boryl migration chemistry,which has been largely developed by Aggarwal and co-workers. [28] In summary,acatalytic enantioselective approach to novel tertiary cyclobutylboronates by conjugate borylation of a-alkyl,b-aryl/alkyl cyclobutenones has been successfully developed.…”
mentioning
confidence: 99%
“…Finally, we explored the versatility of the boronic ester moiety in the benzo‐fused cyclobutenes, since functionalization of less strained cyclobutyl boronic esters has already been described . As depicted in Scheme , spirolactone 11 a could be quantitatively prepared by an oxidation/lactonization sequence .…”
Section: Methodsmentioning
confidence: 99%
“…Finally, we explored the versatility of the boronic ester moiety in the benzo-fused cyclobutenes, since functionalization of less strained cyclobutyl boronic esters has already been described. [8,18] As depicted in Scheme 4, spirolactone 11 a could be quantitatively prepared by an oxidation/lactonization sequence. [19] Zweifel olefination [20] or Matteson homologation [21] enabled the construction of new CÀC bonds, leading to alkene 11 b and boronic ester 11 c in good yields, respectively.…”
mentioning
confidence: 99%
“…We elected to trap 4 as a sulfoxide, since this would potentially offer a stable, solid reagent from which 4 could be conveniently regenerated. 13 Therefore, 4 was trapped with methyl 4-methylbenzenesulfinate (7) to give azabicyclo[1.1.0]butyl sulfoxide 8 in 62% yield (Scheme 1A). Sulfoxide 8 was formed as a single regioisomer, showing that selective deprotonation had indeed occurred, and problems relating to polymerization did not materialize, presumably due to a fast, low temperature lithiation step.…”
mentioning
confidence: 99%